PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PORNOGRAFI MELALUI MEDIA SOSIAL BIGO LIVE BERDASARKAN UNDANGUNDANG NOMOR 19 TAHUN 2016 PERUBAHAN ATAS UNDANGUNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI KEPOLISIAN RESOR KOTA DUMAI - Natasya Alfiana Sagita Saragi; Erdianto Effendi; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Internet media can give birth to new activities that are not fully regulatedby the existing law. This fact has made people aware of the need for regulationthat regulates the activities that involve the internet media. Along with theexistence of internet media in the community developed the internet media alsogave birth to new anxieties, among others the emergence of a new, moresophisticated crime in the form of cyber crime (cyber crime). The purpose ofwriting thesis in, namely First, To know how the law enforcement process and theapplication of sanctions against pornographic crime through social media bigolive based on Law No. 11 Year 2008 About Information and ElectronicTransactions. Second, To know the preventive efforts of government and lawenforcement officers in overcoming the high index of pornographic crime throughsocial media bigo liveThis type of research can be classified in the type of sociological juridicalresearch, because in this study the authors directly conduct research on thelocation or place studied to provide a complete and clear picture of the problemunder study.From the research results of the problem there are two main things that canbe concluded, First,Law Enforcement and Application of Sanctions againstpornography through social media bigo live Based on Law Number 19 Year 2016amendment to Law Number 11 Year 2008 About Information and ElectronicTransaction at the Dumai City Police Force,law enforcement at the Dumai CityResort Police has not been running as it should and the imposition of its sanctionscan’t be imposed directly on the perpetrators. Secondly, the preventive effortsundertaken by the Government and the law enforcement officers of Dumai CityPolice Force are to socialize the dangers and negative impacts of pornographythrough social media to the community.Author's suggestion, Firstly, It takescommitment in law enforcement against pornography through bigo live socialmedia.Keywords: Law Enforcement-Pornography-Dumai City Police Officer